12V car battery to 230VAC power inverter - Hazlan, Md. Rosdan (2009)
Power inverters, regardless of size, are typically constructed of a DC-AC converter. A pure sine wave output will be obtained through the use of a microcontroller and high frequency switching. The microcontroller will be used to digitally drive the transistors on the inverter side of the circuit. This will result in pulses at precise time intervals. The slope and magnitude of the output signal will be exact, as opposed to the unstable signal generated by other power inverters that use analog technology. Implementing the use of a microcontroller also allows for the different alarms and to ensure safety of the user. This power inverter will operate using high frequency switching technology. The harmonics that are produced using high frequency switching will include those near the range of the switching frequency, and those that are of a relatively higher order than the 50 Hz frequency. These harmonics can be isolated using a small low-pass filter. This translates into a much cleaner output signal. Also, the use of high frequency switching will minimize the size of parts used for the construction of the inverter. Future work could be done to further improve efficiency, total harmonic distortion, and size of the power inverter. With these additional improvements, the standard could be raised for future DC/AC power supplies.